The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fvets.2021.740658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Antioxidant and Mineral Status of Rabbits After Administration of Dietary Zinc and/or Thyme Extract

Abstract: This study was aimed at determining the impact of organic zinc (Zn) and thyme extract (TE) administration, given alone or together for 6 weeks, on the antioxidant and mineral status (Zn, Cu, Fe, and Mn) in the plasma and tissues of growing rabbits. A total of 96 rabbits of age 35 days were randomly assigned to one of four treatment groups: a control group (C), a Zn group supplemented with dietary zinc (50 mg/kg), a TE group receiving thyme extract applied in drinking water (1 ml/L), and a Zn + TE group treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Furthermore, Bacova et al (2020) documented that dietary supplementation of thymol (250 mg/kg feed) increased muscle concentrations of oleic acid, MUFA, α-linolenic acid, and docosapentaenoic acid and reduced plasma concentrations of cholesterol, triglycerides, and MDA. These results are in accordance with Kucková et al (2021) who showed that thyme extract added to drinking water (1 ml/L) reduced lipid peroxidation (MDA concentration) in kidney and liver and positively affected the antioxidant response of growing rabbits.…”
Section: Thymesupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, Bacova et al (2020) documented that dietary supplementation of thymol (250 mg/kg feed) increased muscle concentrations of oleic acid, MUFA, α-linolenic acid, and docosapentaenoic acid and reduced plasma concentrations of cholesterol, triglycerides, and MDA. These results are in accordance with Kucková et al (2021) who showed that thyme extract added to drinking water (1 ml/L) reduced lipid peroxidation (MDA concentration) in kidney and liver and positively affected the antioxidant response of growing rabbits.…”
Section: Thymesupporting
confidence: 92%
“…Importantly, several studies proved that dietary Zn supplementation improved nutrients' digestibility including DM, CP, EE, and CF in rabbits (Hafez et al, 2002;Chrastinová et al, 2016;Al-Sagheer et al, 2020;Abdel-Wareth et al, 2020). Moreover, dietary Zn supplementation had a beneficial impact on antioxidant properties, and immune response in rabbits (El-Moghazy et al, 2019;Kamel et al, 2020;Kucková et al, 2021;Hassan et al, 2021b). Kamel et al (2020) elucidated that dietary different Zn sources (50 mg ZnO/ kg diet or 30 mg nano-Zn/ kg diet) elevated serum concentrations of GSH, GST, SOD, immunoglobulins (IgG and IgM), and high-density lipoproteins (HDL-cholesterol), while reduced serum concentrations of triglycerides and MDA in growing rabbits subjected to heat stress conditions.…”
Section: Zincmentioning
confidence: 99%
“…ZnO = Zinc Oxide, n-ZnO = nano-Zinc Oxide, SOD = superoxide dismutase enzyme, CAT = catalase enzyme, T 3 = triiodothyronine, T 4 = thyroxine, AR = androgen receptor gene expression their values were greater (P ≤ 0.05) in the 3 rd group than 2 nd group, throughout the experimental period. Likewise, zinc (Kuckova et al, 2021) and n-ZnO (Abdel-Monem et al, 2021) supplementation in animal feed leads to high antioxidant activities of CAT, GSH-Px, and SOD. In this context, zinc is considered a component of more than 240 enzymes and an essential component in SOD (Prasad, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of dietary thyme to rabbit diets has been shown to significantly improve feed conversion ratio (FCR) by promoting feed intake, boosting body weight, body weight growth, and intestinal health (Placha et al, 2013;Kucková et al, 2021). Additionally, thyme contains antibacterial and antioxidant characteristics.…”
Section: Advances Inmentioning
confidence: 99%